2017
DOI: 10.1016/j.omtm.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of a Lentiviral Vector for Huntingtin Silencing

Abstract: Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder resulting from a polyglutamine expansion in the huntingtin (HTT) protein. There is currently no cure for this disease, but recent studies suggest that RNAi to downregulate the expression of both normal and mutant HTT is a promising therapeutic approach. We previously developed a small hairpin RNA (shRNA), vectorized in an HIV-1-derived lentiviral vector (LV), that reduced pathology in an HD rodent model. Here, we modified this vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 120 publications
(197 reference statements)
2
12
0
1
Order By: Relevance
“…Currently, several strategies are under development to lower huntingtin protein synthesis, and preclinical studies in HD rodent models have demonstrated that lowering mutant huntingtin protein reduces downstream deleterious effects 5, 6, 7. Most approaches of huntingtin lowering aim to decrease translation of huntingtin exploiting the endogenous RNAi mechanism by using synthetic small interfering RNA (siRNA) or by using modified single-stranded antisense oligonucleotides 7, 8, 9, 10, 11, 12, 13, 14. Both siRNAs and antisense oligonucleotides need to be delivered by continuous infusion or repetitive intrathecal injections into the cerebrospinal fluid (CSF), and their therapeutic effect is thought to be most potent in the brain areas adjacent to the ventricular system 7, 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several strategies are under development to lower huntingtin protein synthesis, and preclinical studies in HD rodent models have demonstrated that lowering mutant huntingtin protein reduces downstream deleterious effects 5, 6, 7. Most approaches of huntingtin lowering aim to decrease translation of huntingtin exploiting the endogenous RNAi mechanism by using synthetic small interfering RNA (siRNA) or by using modified single-stranded antisense oligonucleotides 7, 8, 9, 10, 11, 12, 13, 14. Both siRNAs and antisense oligonucleotides need to be delivered by continuous infusion or repetitive intrathecal injections into the cerebrospinal fluid (CSF), and their therapeutic effect is thought to be most potent in the brain areas adjacent to the ventricular system 7, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Next to repetitive infusion of synthetic oligonucleotides, RNAi-based gene therapy approaches using short hairpin RNA (shRNA) and microRNA (miRNA) have been explored as well. RNAi-based gene therapy comprises a single administration of an adeno-associated virus (AAV) or lentiviral (LV) vector, resulting in continuous expression of shRNA or artificial miRNA precursors and subsequent long-lasting huntingtin lowering 5, 6, 12, 13, 17, 18, 19, 20. Intracranial parenchymal injections of artificial miRNA delivered by AAV vectors resulted in huntingtin reduction in HD animal models without signs of toxicity 21, 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…100 Because gene expression signatures are often species-specific, these human-cell-based models have become the preferred test system in parallel to animal studies to study therapy-induced neuronal protection as well as specific off-target silencing of other genes. 71,104 Preclinical Outcome Measures for AAV-miRNA Gene Therapies…”
Section: Cell Systems Modeling Hdmentioning
confidence: 99%
“…et al, unpublished data). 39,64,72,104,144 Measurements of On-Target Lowering Efficacy miRNA-based lowering strategies are designed to lower HTT mRNA levels and thereby reduce the overall mutant HTT protein. Already in early preclinical development, it is essential to establish the on-target activity of therapeutics by measuring their effects on HTT mRNA and protein levels.…”
Section: Evaluating Efficacy For Mirna-based Htt-lowering Therapiesmentioning
confidence: 99%
See 1 more Smart Citation